2022
DOI: 10.1002/jmri.28392
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Sedation/Anesthesia forMRI: Results From the Pediatric Sedation Research Consortium

Abstract: Background: Magnetic resonance imaging (MRI) is the most common imaging procedure requiring sedation/anesthesia in children. Understanding adverse events associated with sedation/anesthesia is important in making decisions regarding MRI vs. other imaging modalities. No large studies have evaluated the practice of pediatric sedation/anesthesia for MRI by a variety of pediatric specialists. Purpose: Utilize a large pediatric sedation database to characterize the patients and adverse events associated with sedati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…Effective management and control of intraoperative and postoperative pain are essential in perioperative hip disease to minimize opioid use and its side effects. In our facility, most pediatric hip surgeries are performed under spinal anesthesia and propofol sedation (12), with preserved spontaneous ventilation. However, the 4-year-old boy had general anesthesia due to the myelomeningocele (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Effective management and control of intraoperative and postoperative pain are essential in perioperative hip disease to minimize opioid use and its side effects. In our facility, most pediatric hip surgeries are performed under spinal anesthesia and propofol sedation (12), with preserved spontaneous ventilation. However, the 4-year-old boy had general anesthesia due to the myelomeningocele (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has been the mainstream medication used by anesthesiologists for sedated MRIs. Propofol, alone or in combination with other medications, appears to be commonly administered also by non-anesthesiologist physicians [10,29]. Advantages are fast induction, good hemodynamic stability and fast recovery allowing patient discharge within 45 min in 99% of cases [30].…”
Section: Anesthesiologist and Non-anesthesiologist Physician Assisted...mentioning
confidence: 99%
“…A retrospective analysis from the Pediatric Sedation Research Consortium showed that anesthesiologist-provided exams accounted for only 9.8% of almost 110,000 sedated MRIs performed in the United States from 2011 to 2017 [10]. Intensivists and emergency physicians were involved more often (49.3% and 29.2%, respectively).…”
Section: Anesthesiologist and Non-anesthesiologist Physician Assisted...mentioning
confidence: 99%
See 1 more Smart Citation
“…Serious adverse events such as pulmonary aspiration of gastric content, cardiac arrest, unplanned admission to ICU and death are rare, whereas minor events such as airway obstructions and desaturations are more common with an incidence ranging from 0.9 to 2.3% and from 0.7 to 3.9%, respectively [5,8 ▪▪ ,9,10]. Other common complications during procedural sedation are related to intravenous access, inadequate sedation, agitation and vomiting [5,8 ▪▪ ]. Adverse events are not only a cause for morbidity and mortality but can also disrupt processes and thus lead to reduced procedural quality.…”
Section: Adverse Events In Paediatric Procedural Sedationmentioning
confidence: 99%